CERAMIC ASSEMBLAGES FROM A FISH-SALTING FACTORY IN TRÓIA (PORTUGAL) - Vaz Pinto, Inêz; Patrícia Magalhães, Ana; Brum, Patrícia (Rei Cretariae Romanae Fautorum Acta, 2024)
Located on a peninsula in the south-western coast of Portugal, the Roman ruins of Tróia are the remains of a large complex of fish-salting factories located in a low area of sand dunes on the border of the river Sado’s estuary. In Roman times it may have been an island facing the ocean, probably the Achale island mentioned by Avienus in the Ora Maritima,in the Roman province of Lusitania. The production complex of Tróia may be considered one of the largest fish-salting production centres in the Western Roman Empire with at least twenty units of production formed by tanks situated around a patio. These units of production are called workshops (oficinas in Portuguese) to distinguish them from factories that would include several workshops and other installations like storerooms.